Prep-Along Facilitated Posterior Crown Preparation in the Preclinical Dental Setting: A Multimedia Approach - Radd W. Lukas (Association of American Medical Colleges, 2019)
Introduction Dental students often seek visual aids and demonstrations when attempting to perform new procedures. This video resource provides an adjunctive teaching tool for a crown preparation on an ivorine molar using the “prep-along” method. This method teaches crown preparation in a uniform, step-by-step manner while providing feedback to students after each step. Methods Prior to the daily simulation clinic session, a calibration session was held for faculty. Following didactic instruction—including principles, criteria, and grading rubric—students participated in the laboratory portion of the course. During this laboratory portion, students viewed a segment of the video, the video was paused, and students attempted that portion of the preparation. The project continued in stages until it was completed. Upon completion, using an electronic grading system, each student performed a self-evaluation, the instructor then performed a blind evaluation, and both student and instructor compared assessments. Results To obtain feedback, an electronic survey was sent to 285 third- and fourth-year dental students. Ninety-four students completed the survey; 94% responded favorably to this method of instruction. Individual comments were also predominantly positive. Discussion Preclinical faculty at the Midwestern University College of Dental Medicine–Arizona use this prep-along for instruction of direct and indirect tooth preparations and restorations. Students participate in this step-by-step process while receiving feedback. Faculty are allowed a structured environment in which to give feedback and instruction at each segment of the preparation. The faculty found that this method of instruction created efficiency and excellence in training surgical hand skills.